Serena vs. Venus: How a Photograph Spotlighted the Fight For Equality - Smith-Llera, Danielle 1971- (North Mankato, MN Compass Point Books, a Capstone imprint, 2017)
Discusses the tennis match between Serena Williams and Venus Williams in the 2001 womens final of the U.S. Open, and the iconic photograph that captured the historic event.
1090
Y
Keywords: Williams, Serena, -- 1981- -- Juvenile literature; Williams, Venus, -- 1980- -- Juvenile literature; Williams, Serena, -- 1981-; Williams, Venus, -- 1980-; Tennis players -- United States; Juvenile literature; African American women tennis players -- Juvenile literature